Pre‐hospital intraosseous use in children: Indications and success rate. (26th October 2021) - Ting, Amy; Smith, Karen; Wilson, Catherine L; Babl, Franz E; Hopper, Sandy M
Abstract: Objective: Intraosseous (IO) needle insertion is an effective method to obtain circulatory access in unwell children. Methods: We conducted a 12‐month retrospective record review of children aged less than 18 years who had a recorded IO attempt by Ambulance Victoria paramedics. Results: Sixty‐five children underwent IO attempt during pre‐hospital care, 60 had IO outcome recorded and were included. 58/60 (96.7%) children had IO successfully placed, 35 were aged <5 years. Cardiorespiratory arrest (39/58, 67.2%) and status epilepticus (11/58, 19%) were the most common indications. Conclusion: While IO placement is uncommonly performed pre‐hospital, in critical situations there is a high success rate.